Roadmap for Structure-based Wakefield Accelerator (SWFA) R&D and its challenges in beam dynamics. (1st May 2022) - Jing, C.; Ha, G.
Abstract: The combination of advantages in positron acceleration over plasma-based accelerators and high gradient over conventional accelerators puts the structure-based wakefield accelerator (SWFA) in a unique spot on the road to a multi-TeV linear collider. As a result of the significant advancements that have been made throughout the past several decades, the SWFA related research continues gaining special attention from the accelerator community. In this article, we will present a survey of the research on SWFAs, with a particular focus on the challenges in beam dynamics, and lay out a roadmap toward its ultimate goal of delivering a mature linear collider design.